Influence Of The Types Of Breastfeeding In The Fusion Of The Palatal Processes In Infants With Cleft Lip And Palate - admin, admin (2018)
Lactancia materna exclusiva y no exclusivaObjective. Determine the relationship between exclusive breastfeeding and fusion of palatal processes, in neonates with unilateral cleft lip palate. Materials and methods. Longitudinal and cohort study, conformed of 2 groups: A) group of study: 4 neonates with unilateral cleft lip palate with exclusive breastfeeding; B) control group: 4 neonates with unilateral cleft lip palate with non-exclusive breastfeeding. To determine the level of fusion of the palatal processes was registry the maxilla with an impression in 3 periods (start, day 10 and day 20). In each model obtained, was measure with a digital caliper the distance between the palatal processes. Results. The level of fusion of the palatal processes in the neonates with exclusive breastfeeding, from start to the day 20 increased 2,44 mm. The level of fusion of palatal processes, in the neonates with non-exclusive breastfeeding, from start to the day 20 increased 2,28 mm. Although with difference statistically doesn’t significative. Conclusion. The exclusive breastfeeding stimulates higher fusion of the palatal processes, in compared the non-exclusive breastfeeding, although the difference is not statistically significative.